Exploring brand personality congruence: measurement and application in the casual dining restaurant industry - Asperin, Amelia Estepa (Kansas State University, 2007)
This study was designed to explore the measurement and application of brand personality congruence (BPC), defined as the gap between the customer’s own personality and a restaurant’s brand personality as perceived by the customer. The study involved two phases: Phase I primarily focused on the development of the BPC scale based on the existing Brand Personality Scale (Aaker 1997), while Phase II involved testing the relationship between BPC and brand loyalty and the mediating effects of satisfaction and trust on that relationship. Both Phases used the online survey methodology for data collection. Confirmatory factor analysis was used to test the dimensionality of brand personality. The five-factor solution was supported with the dimensions of sincerity, excitement, competence, sophistication, and ruggedness. Exploratory factor analysis showed that brand personality dimensions were not stable for measuring customer personality. Only characteristics most closely associated with the Big Five dimensions of agreeableness, extroversion, and conscientiousness significantly loaded on the customer personality scale. A confirmatory factor analysis of the reduced scale resulted in a 5-factor solution: successful, exciting, unique, sincere, and friendly. Because BPC was operationalized as the gap between the customer’s perceived personality and the restaurant’s brand personality as perceived by the customer, only indicators that were common between the two scales were used to establish the 17-item BPC scale consisting of the following dimensions: exciting, unique, sincere, and leader. In Phase II, second-order structural equation modeling was used to test BPC as an antecedent of the post-purchase evaluations of trust, satisfaction, and brand loyalty. Results indicated strong positive relationships, which suggested that higher congruence with the brand’s personality results in increased trust, satisfaction, and brand loyalty. BPC had the greatest direct effect on trust and also had indirect effects on satisfaction via trust and brand loyalty via trust and satisfaction. Additional analyses showed that trust and satisfaction partially mediated the relationship between BPC and brand loyalty. Trust also mediated the relationship between BPC and satisfaction. Results implied that as the restaurant brand earns a customer’s trust over time, the customer’s evaluation of overall satisfaction with the brand also increases and leads to stronger brand loyalty.
Keywords: Brand personality; Brand personality congruence; Brand loyalty; Business Administration, Marketing (0338); Home Economics (0386)